Prognosis of Adults With Isolated Left Ventricular Non-Compaction: Results of a Prospective Multicentric Study - Gerard, Hilla; Iline, Nicolas; Martel, Hélène; Nguyen, Karine; Richard, Pascale; Donal, Erwan; Eicher, Jean-Christophe; Huttin, Olivier; Selton-Suty, Christine; Raud-Raynier, Pascale; Jondeau, Guillaume; Mansencal, Nicolas; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Whether left ventricular non-compaction (LVNC) bears a different prognosis than dilated cardiomyopathy (DCM) is still a matter of debate. Methods From a multicenter French prospective registry, we compared the outcomes of 98 patients with LVNC and 65 with DCM. The primary endpoint combined cardiovascular death, heart transplantation, and hospitalization for cardiovascular events. The two groups presented similar outcomes but different left ventricular ejection fractions (LVEF) (43.3% in LVNC vs. 35.95% in DCM, p = 0.001). For this reason, a subgroup analysis was performed comparing only patients with LVEF ≤ 45%, including 56 with LVNC and 49 with DCM. Results Among patients with LVEF≤ 45%, at 5-year follow-up, the primary endpoint occurred in 33 (58.9%) among 56 patients with LVNC and 18 (36.7%) among 49 patients with DCM (p = 0.02). Hospitalization for heart failure (18 [32.14%] vs. 5 [10.20%], p = 0.035) and heart transplantation were more frequent in the LVNC than in the DCM group. The incidences of rhythmic complications (24 [42.85%] vs. 12 [24.48%], p = 0.17), embolic events, and cardiovascular death were similar between LVNC and DCM cases. Among the 42 patients with LVNC and LVEF > 45%, the primary endpoints occurred in only 4 (9.52%) patients, including 2 hospitalizations for heart failure and 3 rhythmic complications, but no embolic events. Conclusion In this prospective cohort, patients with LVNC who have left ventricular dysfunction present a poorer prognosis than DCM patients. Heart failure events were especially more frequent, but embolic events were not. Patients with LVNC and preserved ejection fraction present very few events in 5 years.